Physical and nutrient characterization of the grains from traditional rice varieties of Kerala and validation of the trait linked molecular markers - George, Jeena; Jayalekshmy, VG; Shahiba, A M; Chacko, Arun; Lachyan, Tejashree S (ORYZA-An International Journal of Rice, 2021)
Kerala is rich with traditional rice varieties that could grow in various agro- climatic conditions of the state. However, many of these traditional varieties are not cultivated and have become extinct due to low yield, promotion of high breed variety seeds and high-cost in continuing the cultivation with traditional seeds. Â The lack of knowledge about the nutraceutical values of traditional rice varieties among farmers leads to the non-participation in cultivation. Present study was aimed at to characterization of thirty traditional rice varieties in terms of physico-chemical, cooking quality as well as molecular screening with markers specific to quality traits. All the varieties used is unique in their quality parameters, among them Njavara Veluthath (13.57%) and Orumundakan (13.35%) were rich in protein content whereas, Karimbalan (311.54 mg/Kg and 102.41 mg/kg) and Veliyan (218.25 mg/Kg and 56.88mg/kg) were superior in Iron and Zinc content. The carotene content ranged from 0.14 mg/100g (Mullan kayama) to 0.56 mg/100g (Njavara veluthath) and amylose content was maximum in Cheruviripp (29.52%). Thus, these varieties need to be conserved and promote them by commercialize and through general public awareness about their medicinal benefits. Correlation analysis showed positive significant relationship between Iron and Zinc content, while amylose content had positive correlation with volume expansion and optimum cooking quality. The SSR marker RM535 linked to Quantitative Trait Loci for Iron and Zinc content was detected in thirteen varieties, RM190 linked with Wx gene locus associated with amylose content in seventeen varieties and the marker RM520 linked to QTL for protein content was detected in all the varieties.